Features of the structural phase state of a weld produced by electron-beam welding in the submicrocrystalline grade 2 titanium alloy; MATEC Web of Conferences; Vol. 143 : Youth, Science, Solutions: Ideas and Prospects (YSSIP-2017) - Kurgan K. A. Kirill Andreevich; Klimenov V. A. Vasily Aleksandrovich; Klopotov A. A. Anatoly Anatoljevich; Gnyusov S. F. Sergey Fedorovich; Abzaev Yu. A. Yury Afanasjevich; Potekaev A. I. Aleksandr Ivanovich; Marzol M. R. Mikhail Romualdovich (2018, 2018)
Title screen